Openness of political structures and gender gaps in protest behaviour in Africa - Eugene Emeka Dim (Cogent Social Sciences)
Protest behaviour has been conceptualized as a high-risk form of political engagement, and it tends to elicit a relatively lower engagement rate than other forms of political participation. In Africa, the risky nature of protests is often complicated by the predominant socio-cultural bias and masculine political norms that hinder women’s political agency. Many of these political systems in Africa are emerging democracies, where women are likely to be marginalized in the civic and political sphere. Using the Afrobarometer data of 2014/2015, this study seeks to examine the impact of the political context on the gender gap in protest behaviour. The study finds that the gender gap in protest behaviour is lower in countries that are politically free and higher in countries with more years of military regimes. These findings offer valuable insights into the political and institutional contexts in which women’s protest behaviour is accentuated and diminished.